AZOSPIRILLUM BRASILENSE INNOCULATION COMBINED WITH DIFFERENT LEVELS OF NITROGEN FERTILIZATION AND ITS EFFECTS IN THE GRAIN SORGHUM SUBJECTED TO WATER RESTRICTION - LIMA DE PAIVA, ANA PAULA; MAGALHÃES, PAULO CÉSAR; DE CARVALHO, LORENA PEREIRA; JALES, HADASSA FORTUNA; GOMES JÚNIOR, CARLOS CÉSAR; DE PAULA LANA, UBIRACI GOMES; MARRIEL, IVANILDO EVODIO (International Journal of Maize & Sorghum, 2022)
One of the major problems in the present scenario is the effect of climate changes and their consequences to the agriculture, mainly due to decreasing water availability. Water restriction is a limiting factor on plants growth, and it can lead to morphophysiological modifications as well as alterations in the plant’s development. Sorghum is a grass widely utilized in agriculture due to its outstanding characteristic of drought resistance, which is higher than the other grasses, therefore being the fifth most sowed grain in the world. The inoculation of growth-promoting rhizobacteria in plants can promote growth and remodel its root system, decreasing the impacts of water restriction. In this sense, this study aims to evaluate the effects of Azospirillum brasilense inoculation in mitigating the water restriction effects in the grain sorghum BRS 332 subjected to two different levels of nitrogen fertilization. Our experiment was carried out in a greenhouse under monitored conditions of temperature and humidity. Plants were treated with two distinct irrigation conditions, two A. brasilense inoculants, one treatment without inoculation, and two levels of nitrogen fertilization (high and low nitrogen fertilization). It was evaluated the differences in their ecophysiological and crop product characteristics. The results showed that plants subjected to drought and associated to rhizobacteria invested in shoot parts, which provided this hybrid higher efficiency between water absorption and loss, and consequently higher stomata efficiency during drought when compared to the control treatment. There was also an increment in the production of the grains, particularly flagrant under lower doses of nitrogen, minimizing the effects caused by drought and decreasing the need to utilize fertilizers.